Septic arthritis of multiple native joints following tooth extraction - Siddegowda, Chidambar; Nanjundappa, Nalina; Japatti, Sharanbasappa; Subramanian, Akshaya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Infection of the distant parts of the body especially the joints after a tooth extraction is uncommon, but when it occurs due to the virulence of the organism or due to the risk factors, it may cause severe joint infection with abscess formation and may limit the movements. We report a case of arthritis of the knee joint along with involvement of other joints following mandibular third molar teeth extraction one week postoperatively. The patient had swelling and limited range of motion of the involved joints, pain over other multiple joints. The patient had two episodes of postoperative septic arthritis following each mandibular third molar extraction. He was diagnosed of having septic arthritis and treated with antibiotics, analgesics, and steroids, that resolved after 3 weeks.